2020
DOI: 10.20546/ijcmas.2020.908.094
|View full text |Cite
|
Sign up to set email alerts
|

Coccinellid Funa Associated with Pulse Crop-ecosystems from Rayalseema Region of Andhra Pradesh

Abstract: Studies were conducted to identify the predatory coccinellid beetle fauna associated with pulse crop ecosystems from Rayalaseema region of Andhra Pradesh. The beetles were collected by sweep netting and hand picking. Male and female genitalia, colouration, characters of elytra, mandibles and antenna were studied for accurate identification of the species. Ten species of coccinellids viz., Cheliomenes sexmaculata (Fabricius), Coccinella transversalis Fabricius, Coccinella septumpunctata Linnaeus, Illeis cincta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…From horticultural and agricultural crop areas in Kashmir, Rasheed and Buhroo [46] gathered thirteen species of ladybird beetles [46]. In vegetable crops from Hyderabadi agricultural fields, Jesu Rajan et al [47] found nine species of coccinellids [47] In the groundnut crop ecosystems of the Rayalaseema Region of Andhra Pradesh, Vasista et al [53] recorded nine species of coccinellid beetles [55]. Six species of coccinellids were found in the kharif rice fields of Rajendranagar, Hyderabad, by Anitha et al [56].…”
Section: Diversity In Indiamentioning
confidence: 99%
“…From horticultural and agricultural crop areas in Kashmir, Rasheed and Buhroo [46] gathered thirteen species of ladybird beetles [46]. In vegetable crops from Hyderabadi agricultural fields, Jesu Rajan et al [47] found nine species of coccinellids [47] In the groundnut crop ecosystems of the Rayalaseema Region of Andhra Pradesh, Vasista et al [53] recorded nine species of coccinellid beetles [55]. Six species of coccinellids were found in the kharif rice fields of Rajendranagar, Hyderabad, by Anitha et al [56].…”
Section: Diversity In Indiamentioning
confidence: 99%
“…Thangjam et al, (2020) observed 19 species of coccinellid beetles belonging to 11 genera, predaceous on sucking pests of king chilli from Assam, India [64] . Vasista et al, (2020) reported 9 species of coccinellid beetles from groundnut crop ecosystems from Rayalaseema Region of Andhra Pradesh [66] . Anitha et al, (2020) recorded 6 species of coccinellids in kharif rice fields of Rajendranagar, Hyderabad [4] .…”
Section: Indian Fauna Of Coccinellidaementioning
confidence: 99%